Leipzig, Warsaw, Krakow. Three funerals of Prince Joseph Poniatowski - Załęczny, Jolanta (Requiem, 2025)
Prince Joseph Poniatowski played an important role in the history of the Poles. His tragic death gave rise to the birth of a national legend. Poniatowski’s life and heroic death made up the image of a hero who was considered a model of loyalty. After his death, he began to be surrounded by reverence, and this was fostered by a number of factors. All the mourning ceremonies, beginning with the bringing of the corpse from Leipzig to Warsaw, through the funeral services and ending with the solemn funeral at Wawel, became occasions for patriotic manifestations. An analysis of the descriptions of the funerals and the sermons delivered will allow us to outline the background for building this legend. The press texts used - in addition to information - also carry a huge emotional charge. Emerging as early as 1813, the legend was systematically enriched and responded to public demand.